Long‐term responses of canopy–understorey interactions to disturbance severity in primary Picea abies forests. (4th November 2017) - Bače, Radek; Schurman, Jonathan S.; Brabec, Marek; Čada, Vojtěch; Després, Tiphaine; Janda, Pavel; Lábusová, Jana; Mikoláš, Martin; Morrissey, Robert C.; Mrhalová, Hana; Nagel, Thomas A.; Nováková, Markéta H.; et al.
Abstract: Questions: How do canopy–understorey interactions respond to variation in disturbance severity over extended periods of time? For forests with different disturbance histories, do light availability and understorey cohort densities converge towards a common old‐growth structure, or do historical legacies influence populations indefinitely? Locations: Remnants of primary spruce ( Picea abies (L.) Karst.) forests throughout Germany, Slovakia, Ukraine and Romania. Methods: A disturbance history of >200 yr was reconstructed from 11 278 tree cores collected from forest plots ( n  = 520). Understorey tree densities of two size classes and hemispherical photo‐based light availabilities were inventoried and modelled as functions of the severity of the main disturbance and time since the event. Results: Variation in understorey tree densities had a hump‐shaped distribution through time. Stem densities were approximately static in the least disturbed sites, and declined in relation to disturbance severity over approx. 100 yr. Similar to patterns of stem densities, initially high understorey light availability also reached a minimum at 100 yr, which indicated crown closure. Following this, light availability and stem densities both increased as stands transitioned from stem exclusion to understorey re‐initiation. The effect of disturbance severity on understorey densities and patchiness in light availability persisted for >200 yr. Conclusions: Long‐term trends in canopy–understorey interactions validate current conceptual models of forest development. Furthermore, we empirically validate that these conceptual models generalized over gradients in disturbance severity. Higher disturbance sites exhibited a more even‐aged character with more pronounced periods of stem exclusion, canopy closure and understorey re‐initiation; forests with low‐severity disturbance histories yielded a more stationary uneven‐aged structure. The model identified the extent of variation in disturbance severity within which these P .  abies forests are able to regenerate and retain their monospecific character, which is increasingly relevant as disturbance regimes continue to shift under global climate change. Abstract : Our study with a long‐term perspective fills an important knowledge gap by simultaneously addressing initial responses of understory cohorts and their reestablishment many decades later. Sapling densities at locations differing in disturbance history converge towards a common baseline, but the effect of disturbance severity on understory densities and patchiness in light availability persisted for more than 200 yr.